La expresión corporal y su influencia en el desarrollo socio afectivo en los niños y niñas de 2 a 4 años del cibv “Estrellitas de la Mañana” en la provincia de Cotopaxi perteneciente al cantón Latacunga parroquia San Buenaventura durante el año lectivo 2014-2015 - Segovia Moreno, Stefanny Carolina (2015)
Nowadays pedagogical education requires teaching tool where students can experience from the reality interdisciplinary understanding knowledge frond efferent areas of study to exert greater commitment and responsibility in their educational work; thereby enabling coexistence and reciprocity of the educational PROCESS. Pedagogical models assume greater responsibility within the educational field ,because the direct and active students and teachers participation and the community in general to the implementation of productive project´s ;pretending meaningful learning It will be achieved only with the practice itself or with student´s daily experience involved in the process .Within the productive projects that are managed ,we carry out activities of body language, which will develop in children´s socio-affective are It involves direct interaction with each of the educational areas of knowledge; promoting interest carrying out activities that help improve the human being quality of life , at kindergarten This research a intends to take appropriate knowledge ,where education community implement each of the steps leading these activities , using them for their own welfare.